Evidence for widespread changes in the structure, composition, and fire regimes of western North American forests. Issue 8 (12th October 2021) - Hagmann, R. K.; Hessburg, P. F.; Prichard, S. J.; Povak, N. A.; Brown, P. M.; Fulé, P. Z.; Keane, R. E.; Knapp, E. E.; Lydersen, J. M.; Metlen, K. L.; Reilly, M. J.; Sánchez Meador, A. J.; et al.
Abstract: Implementation of wildfire‐ and climate‐adaptation strategies in seasonally dry forests of western North America is impeded by numerous constraints and uncertainties. After more than a century of resource and land use change, some question the need for proactive management, particularly given novel social, ecological, and climatic conditions. To address this question, we first provide a framework for assessing changes in landscape conditions and fire regimes. Using this framework, we then evaluate evidence of change in contemporary conditions relative to those maintained by active fire regimes, i.e., those uninterrupted by a century or more of human‐induced fire exclusion. The cumulative results of more than a century of research document a persistent and substantial fire deficit and widespread alterations to ecological structures and functions. These changes are not necessarily apparent at all spatial scales or in all dimensions of fire regimes and forest and nonforest conditions. Nonetheless, loss of the once abundant influence of low‐ and moderate‐severity fires suggests that even the least fire‐prone ecosystems may be affected by alteration of the surrounding landscape and, consequently, ecosystem functions. Vegetation spatial patterns in fire‐excluded forested landscapes no longer reflect the heterogeneity maintained by interacting fires of active fire regimes. Live and dead vegetation (surface and canopy fuels) is generally more abundant and continuous than before European colonization. As a result, current conditions are more vulnerable to the direct and indirect effects of seasonal and episodic increases in drought and fire, especially under a rapidly warming climate. Long‐term fire exclusion and contemporaneous social‐ecological influences continue to extensively modify seasonally dry forested landscapes. Management that realigns or adapts fire‐excluded conditions to seasonal and episodic increases in drought and fire can moderate ecosystem transitions as forests and human communities adapt to changing climatic and disturbance regimes. As adaptation strategies are developed, evaluated, and implemented, objective scientific evaluation of ongoing research and monitoring can aid differentiation of warranted and unwarranted uncertainties.